1994
DOI: 10.1002/jso.2930570207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of desmoglein I in squamous cell carcinoma of the esophagus

Abstract: Desmoglein I (DGI) is major component of the desmosomal membrane core that plays an important role in epithelial cell adhesion. The aim of this study was to explore the correlation between the expression of DGI and the clinicopathological findings of esophageal cancer. DGI expression was immunohistochemically examined using an anti-DGI monoclonal antibody in 139 patients with squamous cell carcinoma of the esophagus. Normal squamous epithelial cells strongly expressed DGI at their cell-cell boundaries. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…Although keratin expression is found in normal squamous cell epithelium and in squamous cell carcinoma, it was not found in the cells of the sarcomatous components of our tumors. The same findings were obtained by the antibodies for epithelial membranous antigen, and by the antibodies for the cell-cell adhesion molecules thrombomodulin [14, 15]and desmosomal glycoprotein 1 [16, 17]. On the other hand, vimentin, a mesenchymal marker, was found in 5 of the 6 tumors.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although keratin expression is found in normal squamous cell epithelium and in squamous cell carcinoma, it was not found in the cells of the sarcomatous components of our tumors. The same findings were obtained by the antibodies for epithelial membranous antigen, and by the antibodies for the cell-cell adhesion molecules thrombomodulin [14, 15]and desmosomal glycoprotein 1 [16, 17]. On the other hand, vimentin, a mesenchymal marker, was found in 5 of the 6 tumors.…”
Section: Discussionsupporting
confidence: 62%
“…Since thrombomodulin was also expressed in the squamous epithelium mainly at intercellular bridges, it is thought to be one of the cell-cell adhesion molecules [14, 15]. Desmosomal glycoprotein 1 is the major glycoprotein component of the membrane core domain of desmosomes which are intercellular junctions in epithelial cell adhesion [16, 17]. Staining results were evaluated by calculating the percentage of positively stained neoplastic cells.…”
Section: Methodsmentioning
confidence: 99%
“…In non鈥恖esional oesophageal mucosal epithelium, DIF studies showed IgG and C3 depositions in the intercellular space, as could be predicted from the known fact that both Dsg3 and Dsg1 are expressed in mucosal epithelium in the oesophagus. Whereas, in cells of SCC, the expression of Dsg1 is markedly reduced or absent, 8,9 in our case, there was some reduced level of deposition in the tumour cells of oesophageal cancer compared with the skin or normal oesophageal membrane.…”
contrasting
confidence: 47%
“…A strong inverse correlation has been found between DG1 expression and tumor invasion, lymph node metastasis, lymphatic invasion, and vascular invasion [23].…”
Section: Adhesion Moleculesmentioning
confidence: 98%